The Impact of Robotic Process Automation on Digital Touchpoints in the Customer Journey: An Analytical Study of the Opinions of a Sample of Decision-Makers at Al-Rafidain Bank in Baghdad (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research aims to identify the effect of Robotic Process Automation (RPA) on digital touchpoints within the customer journey, in its dimensions (functional touchpoints, social touchpoints, and community touchpoints), through surveying and analyzing the opinions of a sample of decision-makers at Al-Rafidain Bank in Baghdad city, totaling (67) individuals. A questionnaire was used as the primary tool for data and information collection from the surveyed sample, and their responses were analyzed using the statistical program SPSS v.28 and SmartPLS 4, to calculate means, standard deviations, relative importance, coefficient of determination (R²), effect size (f²), and simple linear regression coefficient. The study reached several conclusions, the most important of which is the existence of an effect of Robotic Process Automation on digital touchpoints within the customer journey from the perspective of the research sample. The study also presented several recommendations, including the need for decision-makers in the bank to adopt a comprehensive strategy to enhance and employ Robotic Process Automation, including the formation of specialized working committees concerned with developing a roadmap for digital transformation in banking services, implementing training programs aimed at developing employees' capabilities in understanding modern automation applications, and including measurable objectives within the strategy to ensure integration between the administrative and technical aspects in executing automation processes.
Keywords: Robotic Process Automation; Customer Journey; Digital Touchpoints; Al-Rafidain Bank